2019
DOI: 10.1093/humrep/dey373
|View full text |Cite
|
Sign up to set email alerts
|

Complete spermatogenesis in intratesticular testis tissue xenotransplants from immature non-human primate

Abstract: STUDY QUESTION Can full spermatogenesis be achieved after xenotransplantation of prepubertal primate testis tissue to the mouse, in testis or subcutaneously? SUMMARY ANSWER Intratesticular xenotransplantation supported the differentiation of immature germ cells from marmoset ( Callithrix jacchus ) into spermatids and spermatozoa at 4 and 9 months post-transplantation, while in subcutaneous transplants, spermatogenic arrest was observed at 4 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…5 Using testis tissue xenografting models, it has been proposed that limited central vascularization combined with high oxygen and metabolic demands of the implanted cells during re-organization may lead to better development of testicular cords in the peripheral regions of the grafts. 5,38 In our study, only cell implants showed the differential pattern of cordal development, whereas all grafts displayed a uniform distribution of cords. However, in a study using young chicks, auto-transplanted testis tissue grafts maintained tubular structures in peripheral areas and their central areas undergoing necrosis.…”
Section: Discussionmentioning
confidence: 50%
“…5 Using testis tissue xenografting models, it has been proposed that limited central vascularization combined with high oxygen and metabolic demands of the implanted cells during re-organization may lead to better development of testicular cords in the peripheral regions of the grafts. 5,38 In our study, only cell implants showed the differential pattern of cordal development, whereas all grafts displayed a uniform distribution of cords. However, in a study using young chicks, auto-transplanted testis tissue grafts maintained tubular structures in peripheral areas and their central areas undergoing necrosis.…”
Section: Discussionmentioning
confidence: 50%
“…xenotransplantation models. 39 Reports on possible DNA damage and impaired imprinting due to methylation changes might represent risks to the offspring. Three boys in our study had cryopreserved mature spermatozoa obtained from the testicular biopsies in two and from sperm aspiration in one.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, strategies for generating functional sperm in autologous transplants would be preferable. This has been demonstrated in non-human primate models including rhesus monkey (Jahnukainen et al 2012) and marmoset (Luetjens et al 2008, Ntemou et al 2019, which also highlight the importance of the grafting site. For marmoset transplants, spermatogenesis occurred in orthotopic (intratesticular) tissues, but did not occur in tissues grafted ectopically (subcutaneous).…”
Section: Autologous Testicular Tissue Transplantation In Primatesmentioning
confidence: 74%